PENGARUH POSTUR MOTIVASI, KEBIJAKAN PAJAK, PEMAHAMAN WAJIB PAJAK, KUALITAS LAYANAN DAN PENERAPAN SISTEM ADMINISTRASI PERPAJAKAN MODERN TERHADAP KEPATUHAN WAJIB PAJAK ORANG PRIBADI (Studi Kasus pada KP2KP Kabupaten Rembang) - Maharani, Fitri Cahyaning; Rosyidi, Syaiko (JAB (Jurnal Akuntansi & Bisnis), 2017)
The purpose of this research is to explain the influence of motivation posture, tax policy, understanding of taxpayers, service quality, and the application of a modern tax administration system to individual taxpayer compliance. The sampling technique uses purposive sampling. Data collection techniques using survey methods with questionnaires on 125 respondents. The results showed that; Motivational posture and the application of modern tax administration systems have no significant positive effect on individual taxpayer compliance, while tax policies, taxpayer understanding and service quality have a significant positive effect on individual taxpayer compliance. The result of the determination test shows that the adjusted R square coefficient is 0.558, it means that the dependent variable can be explained by an independent variable of 55.8%, and the remaining 44.2% is explained by other factors outside the research model.Keywords: Motivation posture, tax policy, taxpayer understanding, service quality, application of modern tax administration systems and individual taxpayer compliance.